Turizm İşletmelerinde İşgören Seçim Sürecine Yönelik Bir Araştırma - Barakazı, Mahmut (Journal of Business Research - Turk, 2023)
Purpose – The aim of this research is to reveal the conditions and methods by which they determine the employment criteria in the selection process of the employees in tourism enterprises. For this purpose, it is tried to determine how the human resources planning of the job candidates to be employed in tourism enterprises is made and how the workers are researched. In addition, it is determined whether a candidate pool (information of working candidates) has been created and what are the recruitment and selection criteria. Design/methodology/approach – In the process of collecting the targeted data within the scope of the research, semi-structured interview technique was used. In this context, five open-ended questions on the subject to the representatives of the institutions authorized in the selection of employees were directed to the participants in order to be answered. Research data were obtained between 19.08.2022 and 17.10.2022 with the participation of 18 people. The data obtained within the scope of the research were analyzed by content analysis, one of the qualitative research methods. Findings – The opinions of the officials responsible for human resources regarding the employee selection process are explained in terms of categories, and it is seen that the candidates who are compatible with the company goals are perceived more positively. However, it has been found that the external appearance, communication style and general behaviors constitute important details in the employee selection process. It is seen that the professional audit criterion is mostly expressed by all the participants. However, it is understood that the pressure of experience, both in this research and in the related literature, causes great negativities for the employees. Discussion – This research on the human resources managers sample of the employee selection process in tourism enterprises also deals with how employment is realized. In addition, attention is drawn to the connection points between the information revealed in the research with the relevant similarity’s literature and different perspectives.